Customized Prosthetic Oral Rehabilitation of a Child with Hypohidrotic Ectodermal Dysplasia: A Case Report - Hitesh Chander Mittal; Sudhir Bhandari; Ashima Goyal; Aditi Kapur; Krishan Gauba (Journal of South Asian Association of Pediatric Dentistry)
The present case report describes interdisciplinary prosthetic oral rehabilitation of a 7-year-old male child presenting classical features of hypohidrotic ectodermal dysplasia (HED) and subtotal anodontia. The treatment, in this case, was simplified and customized to address various challenges viz. behavioral management, limited hope, low education, and socioeconomic status as well as preserving the erupted two molars. The removable denture was designed to utilize erupted molars for retention with the help of thermoplastic material. The simplification of fabrication steps leads to the successful restoration of a young HED child's masticatory function and esthetics, as well as increased hope and cooperation for future definitive treatment.